Stereoselective synthesis of medium lactams enabled by metal-free hydroalkoxylation/stereospecific [1,3]-rearrangement - Zhou, Bo; Zhang, Ying-Qi; Zhang, Kairui; Yang, Ming-Yang; Chen, Yang-Bo; Li, You; Peng, Qian; Zhu, Shou-Fei; Zhou, Qi-Lin; Ye, Long-Wu (Nature communications, 2019)
Rearrangement reactions have attracted considerable interest over the past decades due to their high bond-forming efficiency and atom economy in the construction of complex organic architectures. In contrast to the well-established [3,3]-rearrangement, [1,3] O-to-C rearrangement has been far less vigorously investigated, and stereospecific [1,3]-rearrangement is extremely rare. Here, we report a metal-free intramolecular hydroalkoxylation/[1,3]-rearrangement, leading to the practical and atom-economical assembly of various valuable medium-sized lactams with wide substrate scope and excellent diastereoselectivity. Moreover, such an asymmetric cascade cyclization has also been realized by chiral Brønsted acid-catalyzed kinetic resolution. In addition, biological tests reveal that some of these medium-sized lactams displayed their bioactivity as antitumor agents against melanoma cells, esophageal cancer cells and breast cancer cells. A mechanistic rationale for the reaction is further supported by control experiments and theoretical calculations. Stereospecific [1,3]-rearrangements are rarely reported method to efficiently build complex organic architectures. Here, the authors describe a metal-free intramolecular hydroalkoxylation/[1,3]-rearrangement sequence affording medium-sized lactams with wide scope, also in an asymmetric fashion.